The Influence of Training Methods and Eye-Hand Coordination Against the Results of Volleyball’s Top Serve Skills - Satardi, Rohandi Nur; Kristina, Putri Cicilia; Handayani, Widya (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aimed to determine: (1) differences in the effect of mass training methods and service distance manipulation methods on the results of volleyball topspin skills and (2) differences in volleyball topspin results with good and low hand-eye coordination. Eye-hand coordination on top spin volleyball skills and (3) training methods and hand-eye coordination on top spin volleyball skills. This research method used an experiment with a 2 x 2 factorial design, with a total of 42 people including coaches from the Citra Dara Volleyball Course Institute. The samples taken from this study were 22 people using a purposive sampling technique. The hand-eye coordination test and the volleyball serve test were used in the research instrument, along with the Russell-Lange volleyball serve test. Data analysis techniques using Anava. The results of this study indicate that: (1) there is a significant difference between the mass training method and the distance manipulation training method in the volleyball top spin results, and (2) there is a significant difference. the result of volleyball peak spin between coaches with high hand-eye coordination and low hand-eye coordination, and (3) training methods and upper server hand-eye coordination affect the results of the game volleyball service.